Q: A plus 2b equals c for a?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

c= a-2b

a-2b=c

A = 2b + cSubtract 'c' from each side:A - c = 2bDivide each side by 2:b = 1/2 (A - c)

3Mgo+2B

a+b+c+d+e = 30 (i) c+e = 14 (ii) d+b = 1 (iii) a = 2b-1 (iv) a+c = 10 (v) By (i)-(ii)-(iii): a = 15 then, by (iv): b = 8 and by (v): c = -5 Also, b = 8 so by (iii): d = -7 and then by (i), e = 19

Related questions

If: a = 2b+c Then: a-c = 2b And: b = (a-c)/2

a = 2b + c then a - 2b = c ie c = a - 2b

2s-2b= a+b+c-2b simplified that would be a+c-b.

c= a-2b

a-2b=c

A = 2b + cSubtract 'c' from each side:A - c = 2bDivide each side by 2:b = 1/2 (A - c)

3Mgo+2B

4

2a + 2b = 26 2b + c = 22 ===> b = 11 - c/2 4c + 2b = 46 ===> b = 23 - 2c From the 2nd and 3rd equations: 11 - c/2 = 23 - 2c 22 - c = 46 - 4c 22 - 46 = -4c + c ===> -24 = -3c ===> c = 8 Substitute c=8 into the 3rd equation: b = 23 - 16 = 7 Substitute b=7 into the 1st equation: 2a + 14 = 26 2a = 12 ===> a = 6

They are terms of an algebraic expression that can be simplified to: 2b+2c

a+b+c+d+e = 30 (i) c+e = 14 (ii) d+b = 1 (iii) a = 2b-1 (iv) a+c = 10 (v) By (i)-(ii)-(iii): a = 15 then, by (iv): b = 8 and by (v): c = -5 Also, b = 8 so by (iii): d = -7 and then by (i), e = 19

a = 2b - c a + c = 2b (a+c)/2 = b b = (a+c)/2